2004
DOI: 10.1093/ageing/afh209
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation improves neuromuscular function in older people who fall

Abstract: vitamin D supplementation, in fallers with vitamin D insufficiency, has a significant beneficial effect on functional performance, reaction time and balance, but not muscle strength. This suggests that vitamin D supplementation improves neuromuscular or neuroprotective function, which may in part explain the mechanism whereby vitamin D reduces falls and fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
256
1
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(281 citation statements)
references
References 33 publications
9
256
1
15
Order By: Relevance
“…In addition to disruption of the bone formation, there is an increased tendency to fall and risk of fracture due to weakness in proximal muscles and impaired neuromuscular co-ordination, which affect quality of life negatively as pain and functional restriction. In several previous studies, a relationship has been shown between vitamin D and physical performance and disability [17,18].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition to disruption of the bone formation, there is an increased tendency to fall and risk of fracture due to weakness in proximal muscles and impaired neuromuscular co-ordination, which affect quality of life negatively as pain and functional restriction. In several previous studies, a relationship has been shown between vitamin D and physical performance and disability [17,18].…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have shown a relationship between vitamin D and physical performance and disability [17,18]. In a study by Başaran et al, which examined the effect of vitamin D level on quality of life by questioning physical and social functions in sub groups, the vitamin D levels were found to be much worse compared to normal individuals [65].…”
Section: Vitamin D and Quality Of Lifementioning
confidence: 99%
“…7 The pharmacokinetics, biochemical effects, efficacy and safety of a single high-dose oral or injectable cholecalciferol has been evaluated and found to be effective safe, and well tolerated. [10][11][12][13][14] There are several unanswered questions regarding the use of different pharmaceutical forms of vitamin D. Because of lack of headto-head comparative studies, it is unclear whether treatment given orally or by injection would be better effective. In order to provide answer to these uncertainties, we carried out head-to-head comparison of same dosage of vitamin D administered by oral and injectable routes of treatment, in achieving normal serum 25OHD level, and assess various ot her biochemical parameters that support adequacy of serum vitamin D levels.…”
Section: Original Articlementioning
confidence: 99%
“…Vitamin D appears to play an important role in neuromuscular function as well as bone density. 27 Meta-analyses have demonstrated that vitamin D supplementation of 700-1,000 IU daily may reduce the risk of falls in the elderly by about 20%, that the effect is achieved in the short term (on the order of 2-5 months), and that the benefit persists for up to 36 months. 28,29 …”
Section: Screening Elderly Patients For the Presence Of Common Geriatmentioning
confidence: 99%